PERTUMBUHAN DAN PRODUKSI JAGUNG (ZEA MAYS L.) VARIETAS PIONEER-12 DENGAN PEMANGKASAN DAUN DAN PEMBERIAN PUPUK NPKMg - Muhammad Fachrozi Surbakti; Sabar Ginting; Jonis Ginting (Universitas Sumatera Utara, 2013)
The aims of this research to know the growth and production of corn (Zea mays L.) Pioneer-12Variety effect of pruning leaves and giving NPKMg fertilizer. This research is implemented ontrying field Tumpatan Nibung village, Batang Kuis, Sumatera Utara, Medan on April 2012 andfinished on Juli 2012. The research was done by using Completely Randomized Design (RAK)factorial consist of two factors treatment. The first factor is pruning with three levels, M0 (withoutpruning), M1 (prune two leaves) and M2 (prune three leaves). The second factor is NPKMgfertilization with four levels, yaitu P0 (0 kg/Ha), P1 (250 kg/Ha), P2 (500 kg/Ha) dan P3 (750kg/Ha). Result of the research show that the pruning treatment effects real against flowering,harvest, weight of dry shelled per sample and hundred weight of seed grain but it does not effectreal against plant height and harvest index. The fertilization treatment effects real against plantheight, flowering, harvest, weight of dry shelled per sample and hundred weight of seed grain but it